Research ethics training, challenges, and suggested improvements across Europe: Radiography research ethics standards for Europe (RRESFE). Issue 4 (November 2022) - Bockhold, S.; McNulty, J.; Abdurakman, E.; Bezzina, P.; Drey, N.; England, A.; Flinton, D.; Khine, R.; McEntee, M.; Mekiš, N.; Precht, H.; Rainford, L.; et al.
Abstract: Introduction: The Radiography Research Ethics Standards for Europe (RRESFE) project aimed to provide a cross-sectional view of the current state of radiography research ethics across Europe. This included investigating education and training in research ethics, and identifying the key challenges and potential improvements associated with using existing research ethics frameworks. Methods: This cross-sectional online survey targeting radiography researchers in Europe was conducted between April 26 and July 12, 2021. Descriptive and analytical statistics were used to identify research ethics education and training trends. Content analysis of qualitative responses was employed to identify significant challenges and proposed improvements in research ethics frameworks of practice. Results: There were 232 responses received across 33 European countries. Most (n = 132; 57%) respondents had received some research ethics training; however, fewer participants had received training on safeguarding vulnerable patients (n = 72; 38%), diversity and inclusivity (n = 62; 33%), or research with healthy volunteers (n = 60; 32%). Training was associated with a greater perceived importance of the need for research ethics review (p = 0.031) and with the establishment of EQF Level 6 training (p = 0.038). The proportion of formally trained researchers also varied by region (p = <0.001). Time-to-ethics-approval was noted as the biggest challenge for professionals making research ethics applications. Conclusion: Early and universal integration of research-oriented teaching within the radiography education framework which emphasises research ethics is recommended. Additionally, study findings suggest research ethics committee application and approval processes could be further simplified and streamlined. Implications for practice: The survey contributes to a growing body of knowledge surrounding the importance of education and training in research ethics for assuring a high standard of research outputs in Radiography and has identified hurdles to obtaining research ethics approval for further investigation and address.